Impact of Rock Cuttings on Downhole Fluid Movement in Polycrystalline Diamond Compact (PDC) Bits, Computational Fluid Dynamics, Simulation, and Optimization of Hydraulic Structures - Lihong Wei; Jaime Honra (Fluids)
The flow occurring at the bottom of a polycrystalline diamond compact (PDC) drill bit involves a complex process made up of drilling fluid and the drilled rock cuttings. A thorough understanding of the bottom-hole flow conditions is essential for accurately evaluating and optimizing the hydraulic structure design of the PDC drill bit. Based on a comprehensive understanding of the hydraulic structure and fluid flow characteristics of PDC drill bits, this study integrates computational fluid dynamics (CFD) with rock-breaking simulation methods to refine and enhance the numerical simulation approach for the liquid–solid two-phase flow field of PDC drill bits. This study further conducts a comparative analysis of simulation results between single-phase and liquid–solid two-phase flows, highlighting the influence of rock cuttings on flow dynamics. The results reveal substantial differences in flow behavior between single-phase and two-phase conditions, with rock cuttings altering the velocity distribution, flow patterns, and hydraulic performance near the bottom-hole region of the drill bit. The two-phase flow simulation results demonstrate higher accuracy and provide a more detailed depiction of the bottom-hole flow, facilitating the identification of previously unrecognized issues in the hydraulic structure design. These findings advance the methodology for multiphase flow simulation in PDC drill bit studies, providing significant academic and engineering value by offering actionable insights for optimizing hydraulic structures and extending bit life.